On Topological Properties of Fuzzy Sequence Space through Orlicz Function - Paudel, Gyan Prasad; Rana, Kesar Singh; Shahi, Nirak Kumar; Baral, Aasis (Darul Yasin Al Sys, 2024)
In this study, a new class of fuzzy number sequences is defined using Orlicz functions, and various useful classes with a variety of structures have been imposed. The behavior of these new classes has been examined as well as their topological properties and relationship to other fuzzy sequences.